Leakage-resilient identity-based encryption scheme. (1st January 2013) - Li, Sujuan; Zhang, Futai
We propose a leakage-resilient Identity-Based Encryption (IBE) scheme in the relative leakage mode. The semantic security of the proposed scheme is proved in two ways in the random oracle model under the Decisional Square Bilinear Diffie–Hellman (D-Square-BDH) assumption. Compared with some existing leakage-resilient IBE schemes, our construction enjoys a shorter parameter length, a lower computation cost and a higher ratio of the key leakage for the same level of security.